Oral health and longitudinal changes in fasting glucose levels: A nationwide cohort study. - Tae-Jin Song; Yoonkyung Chang; Jimin Jeon; Jinkwon Kim (PLoS ONE, 2021)
We investigated the association between oral hygiene indicators of periodontitis, tooth loss, and tooth brushing on the longitudinal fasting glucose level in non-diabetic subjects. Using a nationwide health screening database in Korea, we included non-diabetic individuals who received a health screening program with oral health check in 2009-2010. We constructed a linear mixed model for the longitudinal data of fasting glucose from the baseline to 2015. During the 4.84-year of median follow-up, 91,963 individuals (mean age 56.2 at baseline) underwent 392,780 health examinations with fasting glucose level (mmol/L). The presence of periodontitis was 39.3%. In the multivariate linear mixed analysis, periodontitis was related with increased fasting glucose levels (β = 0.0084, standard error = 0.0035, p = 0.018). Similarly, tooth loss was associated with increased level of fasting glucose (β = 0.0246, standard error = 0.0038, p < 0.001). Compared with tooth brushing ≤2 times/day, tooth brushing ≥3 times/day was associated with decreased fasting glucose levels (β = -0.0207, standard error = 0.0033, p < 0.001). Our data showed that periodontitis and tooth loss were associated with increased fasting glucose levels in non-diabetic individuals. The study findings imply that frequent tooth brushing may reduce fasting glucose levels. Further research is needed to determine the effect of periodontal intervention on glycemic control.